Cyber security of long-range wide-area network (part I) - Tay, Eileen Hui Lian (2018)
Long-Range (LoRa) wireless Wide Area Network is increasingly gaining attention in the world of Internet of Things. One such commercial off-the-shelf technology from Semtech is called LoRaWAN. Its wireless broadcasting nature has incurred many cyber security concerns. One such concern is the possibility of a packet delay attack via wireless jamming and replay attack at the physical layer instead. This attack does not require breaking the packets‟ encryptions but maliciously delay transmission of packets that can cause significant negative impact on time-critical packets. This part I of the project focused on finding the wireless jamming window under various settings to facilitate the replay attack for Part II. By varying the spreading factor, bandwidth and data length, significant change in the jamming window was observed which could drastically reduce the success rate of packet delay attacks when the receiver is in a certain configuration. Patterns and relationships among the various investigated parameters were found and verified. This paper also includes the development of a client-server system that attempts to automate the search for various jamming window which could act as a base for further experiments in the future.